2012
DOI: 10.5897/jphe12.055
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Staphylococcus aureus, coliforms and antibiotic resistant strains of Escherichia coli in rural water supplies in Calabar South Local Government Area

Abstract: An investigation on the incidence of Staphylococcus aureus, coliforms and antibiotic resistantEscherichia coli strains in both treated and untreated rural water supplies was carried out in Calabar South Local Government Area of Cross River State, Nigeria. Analysis revealed significant differences between the different water sources, locations and the months of sampling, with the stream and well water showing higher bacterial contamination compared to the tap water source (P<0.05). The isolation of S. aureus, B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 4 publications
1
8
0
Order By: Relevance
“…Was due to the survival of the fittest depending upon the antibiotics and sampling site. The resistance percentages obtained in this study tally with the resistance ranges found by other authors, Manji and Antai in 2012 [30]; Kumar and Joseph in 2011 [31]. Thus, the Enterococci show very low amoxicillin resistance rates, coinciding with the findings of Fernandes and Watanabe [26].…”
Section: Discussionsupporting
confidence: 90%
“…Was due to the survival of the fittest depending upon the antibiotics and sampling site. The resistance percentages obtained in this study tally with the resistance ranges found by other authors, Manji and Antai in 2012 [30]; Kumar and Joseph in 2011 [31]. Thus, the Enterococci show very low amoxicillin resistance rates, coinciding with the findings of Fernandes and Watanabe [26].…”
Section: Discussionsupporting
confidence: 90%
“…Faecal microorganisms can enter water bodies in diverse ways, including runoff, sewage discharge, and direct faecal deposition (Korajkic et al, 2019). Many investigations have shown the presence of multi-drug resistant coliforms in water (Manji et al, 2012;Mishra et al, 2018;Kurekci et al, 2017;El-Zanfaly, 2015;Azzam et al, 2017). In water reservoirs, such as rivers, streams, lakes and retention reservoirs, both pathogenic and commensal Enterobacterales may be present (Muraleedharan et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Surface waters mostly contain drug-sensitive bacteria, however drug-resistant bacteria are also detected in growing amounts. Antibiotic-resistant bacteria have been detected virtually in all water bodies in the world (Manji et al, 2012;Mishra et al, 2018;Kurekci et al, 2017;El-Zanfaly, 2015;Azzam et al, 2017;Danner et al, 2019). People who use water bodies for recreational purposes constantly expose their skin and mucous membranes to bacteria which may be potentially antibiotic resistant.…”
Section: Introductionmentioning
confidence: 99%
“…27,28 Salmonella enterica is known to cause gastroenteritis, enteric fever, osteomyelitis and diarrhoea in humans and livestock 29,30 while S. aureus, S. epidermidis and S. saprophyticus from the genus Staphylococcus are known to cause skin disease, bacteraemia, wound infections, endocarditis, catheter-related sepsis, UTI, toxic shock syndrome, food poisoning, eye infection and osteomyelitis. 31,32 T. pedis and T. pallidum from the genus Treponema are known to cause dermatitis and syphilis in humans and livestock. 33,34…”
Section: Health Risks Of Detected Zoonotic Bacterial Pathogensmentioning
confidence: 99%